FRI0533 Incidence and risk factors of osteoporotic fracture in patients with rheumatoid arthritis: a multicenter comparative study of the frax criteria and who criteria. (15th June 2017) - Choi, ST; Kwon, S-R; Kim, H-A; Jung, J-Y; Kim, S-S; Kim, S-H; Kim, J-M; Park, J-H; Suh, C-H
Abstract : Background: The fracture risk assessment tool (FRAX) criteria and the bone mineral density (BMD) criteria of the World Health Organization (WHO) are widely used for the assessment of osteoporotic fracture. Rheumatoid arthritis (RA) is the only disease parameter for the evaluation of osteoporotic fracture in the FRAX model, unlike the WHO criteria. However, the input for RA is just a dichotomous variable in FRAX model. Objectives: In this study, we evaluated the incidence and risk factors of osteoporotic fracture in patients with RA through the comparison of the FRAX criteria and WHO criteria. Methods: This study is a multicenter study, including 479 RA patients in 5 hospitals and 384 healthy controls, between January 2012 and December 2016. All of the RA patients fulfilled the 1987 American College of Rheumatology (ACR) criteria or the 2010 ACR/European League Against Rheumatism (EULAR) criteria for RA. The FRAX criteria for high risk of osteoporotic fracture, which is a 10-year probability of ≥20% for major osteoporotic fracture or ≥3% for hip fracture, were calculated by the FRAX tool including the BMD values. The classification of osteoporosis, according to WHO criteria were based on T-score ≤ -2.5. We assessed various demographic factors, clinical and laboratory findings of RA, and medication use for RA and osteoporosis, and then evaluated the incidence and risk factors for osteoporotic fracture. Results: The mean age of RA patients was 61.7±11.9 years, and 426 patients were female (88.9%) with 353 postmenopausal women (82.9%). The BMD score of L-spine in RA patients was significantly lower than that in healthy control (-2.21±1.41 vs. 0.97±0.11, p <0.001). Osteoporotic fracture was detected in 81 (16.9%) patients with RA. In RA patients, 226 (47.2%) patients met the FRAX criteria for high risk of osteoporotic fracture, and 240 (50.1%) patients satisfied the WHO criteria. The result of the FRAX criteria was affected by the female sex, menopause, smoking, drinking, higher dose of glucocorticoid (≥5mg/day), vitamin D use, calcium use and proton pump inhibitor (PPI) use ( p <0.05). In multiple linear analysis, the FRAX score to 10-year probability of ≥3% of hip fracture was associated with age (β=0.384, p <0.001), body weight (β=-0.110, p =0.038), erythrocyte sedimentation rate level (β=0.125, p =0.010), glucocorticoid dose (β=0.105, p =0.024), and PPI use (β= -0.123, p =0.010). The independent risk factors for FRAX criteria were age (OR 1.160, p <0.001), female sex (OR 3.942, p =0.010), body mass index (BMI) (OR 0.869, p =0.001), glucocorticoid dose (OR 1.167, p =0.025) and PPI use (OR 2.552, p =0.019), and those for WHO criteria were age (OR 1.021, p =0.040), glucocorticoid dose (OR 1.109, p =0.046) and smoking (OR 2.924, p =0.031). Conclusions: Osteoporotic fractures were found in 16.9% of RA patients. The proportion of patients with high risk of osteoporotic fracture was 47.2% in the FRAX model and 50.1% in the WHO model. Age, female sex, lower BMI, higher dose of glucocorticoid, PPI use and smoking were independent risk factors for osteoporotic fracture in RA patients. Disclosure of Interest: None declared